Green Economy Dalam Prespektif Maqashid Syariah - Eni Haryani Bahri (TANSIQ: Jurnal Manajemen dan Bisnis Syariah, 2022)
This article to describe the Green Economy concept in Indonesia from Maqashid al-Shari’ah perspective. With analysis method of library research, this paper describes how the Green Economy concept is applied in the Maqasid Syari'ah perspective, namely protecting religion, soul, mind, lineage, property and the environment. The results show that the green economy is in accordance with the goals, basic principles and systems of Islamic economics, that is to improve human welfare in the direction of improving the quality of human life and nature. In Islam the ultimate goal in all human activities has been contained in maqashid sharia by seeking five forms of safeguarding namely hifdz al-din, hifdz al-aql, hifdz al-nafs, hifdz al-maal and hifdz al-nasl, including in carrying out economic activities by keep the environment. In designing an implementable, reliable and comprehensive Green Economy implementation model, Indonesia should have an economic model that is truly green and relevant to the characteristics of the Indonesian nation. The principle of low carbon is basically in line with the maintenance of the soul and mind. The principle of resource efficiency is also in line with the maintenance of offspring and wealth. Also, the socially inclusive principle is found in the five aspects of maintenance in the concept of maqashid al-shari'ah.